1991
DOI: 10.2527/1991.69124810x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine on growth, carcass traits, and fasting heat production of U.S. contemporary crossbred and Chinese Meishan pure- and crossbred pigs1

Abstract: Twenty-four U.S. crossbred (Duroc x White composite; D x Wc; 83.9 kg), 24 purebred Meishan (M; 59.4 kg), and 24 Meishan x White composite crossbred (M x Wc; 83.4 kg) barrows were allotted within genotype to a 16% CP corn-soybean meal diet or this basal diet + 20 ppm of ractopamine and allowed ad libitum access to feed for 52 d. No genotype x ractopamine interactions were detected (P greater than .05) in pigs for growth, lean cuts, ham and loin characteristics, leaf fat and visceral organ weights, fasting whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…The activity of enzymes for lipid synthesis shows maximal values between 40 and 60 kg body weight in fast growing pigs, with marked differences according to the anatomical localization of the fat depot and breeds (Hood and Allen, 1973). Pietrain, which is recognized as one of the leanest breeds (Bidanel et al, 1994) and Meishan, which exhibits one of the highest degrees of adiposity (Yen et al, 1991 (Mersmann et al, 1976;Henry, 1977 (Camara et al, 1994 (Hausman and Martin, 1981) and the same is true for Large White pig compared to Pietrain (Moody et al, 1978). Later in life, after 45 days, the adipocyte size in Meishan pig is larger than that of Large White (Camara et al, 1994 Lee and Kauffman, 1974;Hood and Allen, 1977;Moody et al, 1978) and was observed also in bovine species (Chakrabarty and Romans, 1972;Lin et al, 1992 (Chora et al, 1995).…”
mentioning
confidence: 99%
“…The activity of enzymes for lipid synthesis shows maximal values between 40 and 60 kg body weight in fast growing pigs, with marked differences according to the anatomical localization of the fat depot and breeds (Hood and Allen, 1973). Pietrain, which is recognized as one of the leanest breeds (Bidanel et al, 1994) and Meishan, which exhibits one of the highest degrees of adiposity (Yen et al, 1991 (Mersmann et al, 1976;Henry, 1977 (Camara et al, 1994 (Hausman and Martin, 1981) and the same is true for Large White pig compared to Pietrain (Moody et al, 1978). Later in life, after 45 days, the adipocyte size in Meishan pig is larger than that of Large White (Camara et al, 1994 Lee and Kauffman, 1974;Hood and Allen, 1977;Moody et al, 1978) and was observed also in bovine species (Chakrabarty and Romans, 1972;Lin et al, 1992 (Chora et al, 1995).…”
mentioning
confidence: 99%
“…Williams et al (1987) reported a reduction in liver size (P B0.05) in veal calves fed cimaterol. Pigs fed ractopamine also showed decreased weight (P B0.05) of heart, lung, kidney and pancreas (Yen et al 1991). As organs have considerably higher metabolic rates than skeletal muscle and account for 30(60% of whole body energy needs (Reynolds et al 1991), this tendency for a reduction in visceral organ mass may offset the increased heat production that would normally be associated with bAR agonist treatment, as a result of increased muscle mass and weight gain, thus accounting for the lack of change in heat production values seen in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the reduction in the efficiency deposition associated with ractopamine treatment was the result of an increase in basal metabolic rate. Yen et al (1991) reported that it had no effect on postprandial whole-animal heat production in pigs. Also, a study by Ferná ndez et al (1998) found that salbutamol did not alter energy metabolism in swine and concluded that the detected differences in energy retention were a consequence of the modified protein and fat deposition pattern.…”
Section: Efficiency or Energy And Protein Depositionmentioning
confidence: 99%